Effect of a Lactic Acid Bacteria Based Probiotic, FloraMax-B11®, On Performance, Bone Qualities and Morphometric Analysis of Broiler Chickens: An Economic Analysis - Gutierrez-Fuentes, Claudia E.; Zuniga-Orozco, Luis A.; Vicente, Jose Luis; Hernandez-Velasco, Xochitl; Menconi, Anita; Kuttappan, Vivek Ayamchirakkunnel; Kallapura, Gopala; Latorre, Juan David; Layton, Sherry; Hargis, Billy Marshall; Tellez , Guillermo (International Journal of Poultry Science, 2013)
Probiotics are live microorganisms which, in adequate dose, will increase the beneficial microbial population in gut. A commercial lactic acid bacteria-based probiotic FloraMax-B11® (FM) has shown to have beneficial effect in reducing microbial colonization in broilers. The present study was intended to evaluate the effect of FM on growth performance, bone qualities and morphometric analysis of broiler chickens. In experiment 1, broiler chickens were divided into control or FM treated chickens. Treated chickens received 5 doses of FM. At the end of 30 days, body weight, was recorded and all chickens were humanely killed. Tibias and ileum content were collected. A significant (p